Long-term hip function in slipped capital femoral epiphysis treated with in situ pinning. (11th January 2019) - Bond, Elizabeth C; Phillips, Paul; Larsen, Peter D; Hunt, Lynette; Willoughby, Richard
Background: In recent years, there has been a trend toward more aggressive management of slipped capital femoral epiphysis (SCFE) with acute anatomical realignment; however, the literature is unclear with regard to the indications for this. Questions/purposes: To collect long-term patient-reported outcome scores on a group of SCFE patients using modern hip scores. The second aim was to determine whether there is a threshold level of deformity beyond which patients have predictably poor outcomes following in situ pinning. Patients and methods: Patients presenting with SCFE between 2000 and 2009 completed a survey consisting of three modern hip scores and were classified into poor, intermediate, and good outcome groups. The posterior slope angle (PSA) was used to measure slip deformity. We examined the relationship between patient characteristics and functional outcomes. The relationship between PSA score and overall outcome was examined using receiver operator curve (ROC) analysis. Results: The total study population was 63; 14% patients had poor, 29% had intermediate, and 57% had good functional outcomes. The mean Non-Arthritic Hip Scores (NAHSs) for those with poor outcomes was 51, 76 in the intermediate group, and 95 in the good group ( p <0.001). PSA was significantly lower in those with good functional outcomes. ROC analysis demonstrated that a higher PSA was moderately predictive of a poor clinical outcome (area under the curve of 0.668). In both the poor and intermediate outcome groups, 50% of patients had a PSA of 40° or greater, whereas only 31% of those with good clinical outcomes had PSA of 40° or greater. Conclusions: A significant proportion of post-SCFE patients have ongoing suboptimal hip function after pinning in situ. Those with a PSA more than 40° have a higher chance of a poor outcome.